Solusi Numerik Metode Beda Hingga Aplikasi Excel Untuk Solusi Lendutan Balok Beton Sederhana - Yoh, Wahyo Hendarto (Jurnal Matematika; Vol 7 No 1 (2017), 2017)
The use of worksheets in Excel is one of the tools for   learning in solving  the mathematical problems .  At generaly the  solution of mathematical problem ussually is solved by the soft ware aplication, that sure  used  high  level programming languages like FORTRAN, BASIC, C++, MATLAB, etc. However  the use of   worksheet in Excel rather more familiar than using the software aplication for the students. It is caused  the students must be able to know  how  to write the code program that obtained product the listing program.  One of the  most  problematic on civil engineering is about concrete beam structure deflection.   The mathematical analysis simple  beam structure deflection is presented by the ordinary differential equation second order non  linier and the other name  it’s called poisson equation.   The  aim of this article  for : (1) To give the learning assistance to the student  when they aren’t use the soft  ware program and beside to rise creation  the application spreadsheet as tool for numerical  solution by finite difference   method on simple beam deflection. (2) To evaluate the error result comparation of numeric solution and analytic  solution.(3)To give the understanding  about numerical method that accordance with simple beam deflection problem on civil engineering education  and mathematical education. Keywords :   Fungsi Internal EXCEL, Metode Beda Hingga. Persamaan Garis Elastika.